Structural Behaviour of Beam to Concrete-filled Elliptical Steel Tubular Column Connections. (February 2017) - Yang, J.; Sheehan, T.; Dai, X.; Lam, D.
Abstract: Elliptical hollow sections (EHSs) have been utilized in construction recently because of their visual appearance as well as the potential structural efficiency owing to the presence of the two principle axes. However, little information currently exists for the design of beam to elliptical column connections, which is an essential part of a building structure. Thus, to ensure the safe and economic application of EHSs, a new research project has been initiated. Rotation behaviour of simply bolted beam to concrete-filled elliptical steel column connections was investigated experimentally. Various joint types were considered and the benefits of adopting core concrete and stiffeners were highlighted. This paper covers the experimental studies and simulation of the connections using the ABAQUS standard solver. Comparisons of failure modes and moment vs. rotation relationships of the connections between numerical and experimental results were given. Good agreement has been obtained and the developed finite element model was therefore adopted to conduct a preliminary parametric study to explore the effect of critical parameters on the structural behaviour of beam to concrete-filled elliptical column connections.